Mitochondrial outer membrane forms bridge between two mitochondria in Arabidopsis thaliana. (3rd May 2016) - Yamashita, Akihiro; Fujimoto, Masaru; Katayama, Kenta; Tsutsumi, Nobuhiro; Arimura, Shin-ichi
ABSTRACT: Mitochondria are double-membrane organelles that move around and change their shapes dynamically. In plants, the dynamics of the outer membrane is not well understood. We recently demonstrated that mitochondria had tubular protrusions of the outer membrane with little or no matrix, called MOPs (mitochondrial outer-membrane protrusions; MOPs). Here we show that a MOP can form a bridge between two mitochondria in Arabidopsis thaliana. The bridge does not appear to involve the inner membranes. Live imaging revealed stretching of the MOP bridge, demonstrating the flexibility of the outer membrane. Mitochondria frequently undergo fission and fusion. These observations raise the possibility that MOPs bridges have a role in these processes.